Comparison of Cardiac Indices Using Two Different Concentrations of Topical Adrenaline during Endoscopic Transsphenoidal Pituitary Surgery: A Prospective Randomized Observational Study - Gautam, Archana; Haldar, Rudrashish; Srivastava, Shashi; Gupta, Devendra; Jaiswal, Awadhesh Kumar; Mishra, Prabhaker (Asian Journal of Neurosurgery, 2023)
Introduction Adrenaline-soaked wicks are often employed to decongest nasal mucosa during transsphenoidal pituitary surgeries to ensure proper hemostasis and visibility of the operating field. Considerable debate exists regarding the optimum concentration of adrenaline that strikes a balance between hemostasis as well as the hemodynamic side effects of adrenaline. This study assessed cardiac indices like cardiac output and cardiac index using a FloTrac Vigileo cardiac output monitor to compare two different concentrations of adrenaline used for topical instillation.Materials and Methods 60 adult patients undergoing transsphenoidal pituitary surgery were randomly assigned to receive cotton wicks soaked in adrenaline solution (either 1:100,000 or 1:200,000) for nasal decongestion. Following a standardized anesthetic regime, a FloTrac Vigileo cardiac output monitor was attached with the invasive arterial line for precise monitoring and recording of cardiac indices (cardiac output and cardiac index). Additionally, quality of surgical field (as reported by the operating surgeon) blood loss, incidences of adverse hemodynamic events, and rescue drug usage were recorded.Results No difference in cardiac outputs and cardiac indexes of the patients was observed during baseline to 55 minutes and at 80 minutes and onward, whereas difference rose to statistical significance at the time points of 60 minutes and 70 minutes (p < 0.05). Other parameters like stroke volume, stroke volume variation, and hemodynamic parameters were similar. Quality of the surgical fields (as reported by the surgeon), intraoperative bleeding, incidences of adverse effects, and frequency of rescue drugs usage were similar.Conclusion Instillation of 1:100,000 dilution of adrenaline solution compared with 1:200,000 for nasal decongestion is associated with significant rise in cardiac output and cardiac index at 60 and 70 minutes of the surgery with similar blood loss and hemodynamic variables. Therefore, the lower concentration of adrenaline can be recommended for usage during transsphenoidal pituitary surgeries.
Keywords: blood pressure; catecholamine; epinephrine; hemostasis; pituitary; vasoconstriction